Video Steganography Based on Modified Embedding Technique (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Information security has become the concern of the most famous researchers and the focus of their attention, as they are constantly trying to find the best and most secure way to transfer information through a secure channel to protect it from hacking attempts and common attacks on the Internet. This work is an attempt to suggest a security approach in protecting data by focusing on protection the text sent in Arabic and English from being noticed or modified by attackers, and it is efficiently hidden inside the cover video. the proposed method combines cryptography and steganography by encrypting the secret text before hiding it with the public key encryption system is named after the initials of its co-founders, Rivest - Shamir – Adleman (RSA). In addition, add an extra layer of security and confidentiality, a hash-based least significant bit mechanism that uses a pattern to choose the insertion sites in the least Significant Bit (LSB). In a spatial domain technique, the secret information is embedded in the LSB of the cover frames that are efficiently chosen based on the hash value of the secret key agreed upon between sender and receiver. The secret information is divided into eight bits and then embedded in the Red, Green, and Blue (RGB) pixel values of the cover frames. In comparison to the original cover video, the proposed method is analyzed in terms of both "Peak Signal to Noise Ratio (PSNR) reached to scale (68.582) compared to the original cover video as well as the Mean Square Error (MSE) reached to scale (0.0115) through embedding message with size 2 KB in AVI video. When compared to other ways of concealing common information, the experimental results from our methodology show that it provides stronger embedding capacity as well as improved imperceptibility of stego-videos and boosts security and robustness.